(3LGeY GdJYQjH HGdWQjb GdbQjHs ((3YHO GdcQje Hf CMeO Hf eMeO GdCWQGHdSi GdNdhJi GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi UGf HdZI GdYQH GdcJGH hGdSfI CeG HYO , aEfi HYO Cf hbaJ Ydi cJGH GdeYQH EHOGY GdCSJGP CHj GdefUhQ GdLhGdjbi cGf eMJGL Edi JJeI ai GdJQJjHJ HGH GdgeRg eY GdCda s
(3BNQgG (B:s
(3adjYQa GdaQb Hjf bhdc ghOkG HZjQ jGA , hjghOjkG HGdjGA hGdJfhjf hjghO HZjQ Jfhje aEf GdaQb Hjfge dWja , hGdhLg MSf WQja gPG BNQ eG JjSQ ef JNdjU GdJQJjH hGdJPjjd hYfO hMOJi CfjS Je cJGHI s
(3ai GdfSNI GdChdi Qbe (B" 103 " (3Yde dZI CfgG efShHI ddTHjTis
(3hdG Odjd Ydi Pdc hCf GdHTHjTi dg (B" (3GdJPdjd hGdJcejd (B" (3Qbe (B" 377"s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs